Analisis Potensi Outdoor Education Tracking di Kabupaten Sumedang Berdasarkan Marketability, Sustainability, Participation, dan Disaster Mitigation - Rakafadni Historian; Aam Ali Rahman; Ayi Suherman; Rizal Ahmad Fauzi; Dewi Susilawati (CV. Global Cendekia Inti, 2026)
Sumedang Regency has great potential for developing tracking-based sport tourism due to its mountainous geography and improved regional connectivity through the construction of the Cisumdawu Toll Road. However, the management of this sport tourism has not been well integrated, particularly in terms of hiking trail management, facilities, and community participation. This study aims to explore the phenomenon of tracking in Sumedang through the MSP+DM (Man, Sport, Place, and Destination Management) approach to identify the most potential mountains, provide recommendations for superior tracking destinations, identify optimal facilities, and formulate strategies to increase tourist visits. This study employed a qualitative approach with a phenomenological design, focusing on three tracking destinations in Sumedang Regency, namely Mount Manglayang, Mount Kerenceng, and Mount Tampomas. Informants consisted of hikers, guides, trail managers, and tourism officials. Data were collected through in-depth interviews, participatory observation, and documentation, and subsequently analyzed using the Moustakas phenomenological model. The findings reveal that Mount Manglayang excels in marketability and accessibility, Mount Kerenceng demonstrates strengths in sustainability through strong community participation, while Mount Tampomas stands out in visitor participation and the preservation of local cultural values. These findings indicate that the development of sport tourism in Sumedang should prioritize strengthening digital promotion, improving environmentally friendly facilities, and enhancing collaboration among local communities, tracking organizations, and government stakeholders. This study contributes to expanding the understanding of phenomenology-based sport tourism in Indonesia and provides an empirical foundation for the development of sustainable eco-sport tourism destinations.